Formed Egg Shell Catalyst for Steam Reforming of Methanol

KR103014247B1Active Publication Date: 2026-09-18IND FOUND OF CHONNAM NAT UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020230122046
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2026-09-18
Estimated Expiration
2043-09-13

Smart Images

  • Figure 112023101552902-PAT00011_ABST
    Figure 112023101552902-PAT00011_ABST
Patent Text Reader

Abstract

The present invention provides a mesoporous alumina-supported copper-zinc eggshell catalyst and a molded body thereof capable of catalyzing a methanol steam reforming reaction. Furthermore, the present invention provides a method for manufacturing such an eggshell catalyst and a molded body thereof. Such a copper-zinc eggshell catalyst can suppress carbon monoxide generation more effectively and exhibit higher reaction activity than a homogeneously supported catalyst with the same copper loading.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a catalyst for a hydrogen production reaction. Specifically, the present invention relates to a catalyst for catalyzing the steam reforming reaction of methanol and a method for manufacturing the same. Background Technology

[0002] Hydrogen, which can be used as fuel for polymer electrolyte membrane fuel cells (PEMFCs), is an important means for decarbonized energy production; however, there are many limitations in storing and transporting gaseous hydrogen. These limitations can be overcome by utilizing appropriate catalysts to produce hydrogen on-site from other chemical raw materials ( in situ Most of this can be resolved by producing hydrogen. Among the candidates for raw materials to produce hydrogen on-site, methanol offers several advantages. As a hydrogen feedstock, methanol is liquid at room temperature, making storage and management convenient. Additionally, for hydrogen production reaction feedstocks, a high proportion of hydrogen to carbon is advantageous, and methanol has the highest proportion among alcohols. Methanol also has price competitiveness as a feedstock because it can be obtained through various production routes. Although the methanol steam reforming reaction, which produces hydrogen from methanol, has the advantage of proceeding at a relatively low temperature of less than 350°C, considering only the cost of hydrogen production, the methanol steam reforming reaction is still more expensive than the hydrogen produced from natural gas reforming. Therefore, the development of high-performance, low-cost, and effective reaction catalysts is necessary to overcome this.

[0003] In the process of producing hydrogen by methanol steam reforming, the main reaction in which methanol and steam react to produce carbon dioxide and hydrogen, and

[0004]

[0005] In addition to this, the decomposition reaction of methanol and as a reaction that produces carbon monoxide

[0006]

[0007] The reverse reaction of the water gas shift

[0008]

[0009] This can occur. Since carbon monoxide acts as a catalyst poison for platinum, an active ingredient used in fuel cells, the standards for hydrogen used in fuel cells are strict, requiring the carbon monoxide impurity content to be less than 10 ppm. Therefore, additional processes are required to reduce the carbon monoxide content of hydrogen used in fuel cells; generally, hydrogen feedstock with a carbon monoxide content of 1.0% or less can be treated using the pressure swing adsorption (PSA) method, which is widely used for carbon monoxide reduction. Consequently, it is important for the catalyst in the methanol steam reforming reaction to have a high methanol-to-hydrogen conversion rate while suppressing carbon monoxide generation to less than 1.0%.

[0010] To achieve such high purity and high methanol conversion rates, precious metals such as platinum or other metallic components, as described in U.S. Patent Publication No. 20140308597, could be used; however, since these methods lack cost competitiveness, there is an urgent need for highly active catalysts utilizing inexpensive catalytic active materials such as copper. Furthermore, even when catalysts are manufactured using inexpensive active material raw materials, the fact that active sites within the catalyst that are not substantially utilized for the catalytic activity of the reactants remain wasted leaves room for improvement. This problem is particularly pronounced in catalysts where the catalytic active material is uniformly distributed within the catalyst structure. For example, it has been revealed that in the case of a spherical methanol steam reforming catalyst with a diameter of 3 mm in which the active material is uniformly distributed, the portion utilized for the reaction is only 40% of the outer region. International Journal of Hydrogen Energy , Vol. 47, No. 14 (2022), pp. 8700–8715).

[0011] In addition, for the use of catalysts in industrial-scale reactors, it is advantageous for the catalyst to be a molded body such as a spherical, rectangular, or cylindrical shape, or a pellet-shaped catalyst. However, if the catalyst is pelletized from a finished catalyst material, there is a problem in that the activity of the catalyst material may decrease during the process. Prior art literature

[0012] U.S. Patent Publication No. 20140308597

[0013] Zhu et al. <The role of effectiveness factor on the modeling of methanol steam reforming over CuO / ZnO / Al2O3 catalyst in a multi-tubular reactor> , International Journal of Hydrogen Energy, Vol. 47, No. 14 (2022), pp. 8700–8715 The problem to be solved

[0014] The technical objective of the present invention is to provide a catalyst for a methanol steam reforming reaction that exhibits good methanol conversion rate and suppression of carbon monoxide generation without the use of expensive catalytic active materials. Another technical objective of the present invention is to provide a simple manufacturing method for producing such a catalyst. means of solving the problem

[0015] In one aspect of the present invention, a copper-zinc eggshell catalyst supported on a mesoporous alumina carrier for methanol vapor reforming and a molded catalyst body are provided. The eggshell catalyst or molded catalyst body of the present invention is a catalyst or molded catalyst body containing zinc (II) and copper supported on a molded mesoporous alumina carrier, and is composed of a center and an outer layer surrounding the center, wherein the copper in the catalyst or molded catalyst body is substantially present only within the outer layer, the ratio of its thickness to the major axis length of the catalyst body is 0.30 to 0.54, and the amount of copper supported in the catalyst or molded catalyst body is 0.85 weight% to 2.8 weight% based on the total weight of the catalyst body. Depending on the reduction treatment, the form of copper contained in the copper-zinc eggshell catalyst of the present invention may be divalent copper (II) or metallic copper (O).

[0016] In another aspect of the present invention, a method is provided for producing a copper-zinc eggshell-shaped catalyst or a catalyst molded body supported on a mesoporous alumina carrier capable of catalyzing a methanol steam reforming reaction. The method for producing the catalyst according to the present invention

[0017] (1) A hydrophobic immersion step in which mesoporous alumina is immersed in a solvent selected from the group consisting of ethylene glycol, propylene glycol, diethylene glycol and glycerol, or a mixture of these solvents,

[0018] (2) An impregnation step in which the mesoporous alumina that has completed the hydrophobic immersion step is immersed in an aqueous solution containing a copper precursor and a zinc precursor containing 0.5 to 2 times the number of moles of copper atoms in the copper precursor.

[0019] (3) A drying step for drying the mesoporous alumina after the above impregnation step and

[0020] (4) Includes a calcination step of calcining the dried mesoporous alumina. Effects of the invention

[0021] The mesoporous alumina-supported copper-zinc eggshell catalyst of the present invention exhibits higher catalytic activity in the methanol steam reforming reaction and can better suppress the formation of carbon monoxide byproducts compared to a homogeneous supported catalyst with the same copper loading. For this reason, the copper-zinc eggshell catalyst of the present invention enables the production of hydrogen of a purity suitable for purification via pressure swing adsorption. Furthermore, since the copper-zinc eggshell catalyst of the present invention has a structure in which copper is contained substantially only in the outer layer, it can reduce the amount of metals such as copper compared to a homogeneous supported catalyst with the same catalytic activity. Additionally, it offers excellent economic efficiency because it can be easily formed into a mesoporous molded body or pellet without a decrease in catalytic activity through a simple manufacturing method utilizing the incompatibility between hydrophobic solvents and water. Brief explanation of the drawing

[0022] FIGS. 1a, 1b, 1c, and 1d are optical microscope images showing cross-sections of eggshell-shaped alumina-supported copper-zinc catalyst molded bodies prepared by repeatedly impregnating them 5, 4, 3, and 2 times, respectively, with a hydrophilic impregnation solution containing copper in an amount of 0.5 wt% relative to the total weight of the catalyst. Figure 1e is a graph showing the distribution of copper and zinc loading across the diameter of the catalyst molded body starting from one surface of Figure 1a, based on energy dispersive spectral analysis. Figure 1f is a graph showing the distribution of copper and zinc loading across the diameter of the catalyst molded body shown in Figure 1c, starting from one surface of the molded body, using energy dispersive spectral analysis. Figure 2a is an optical microscope image showing a cross-section of a copper-zinc catalyst molded body uniformly supported on an alumina carrier. FIG. 2b is an optical microscope image showing the cross-section of a uniformly supported copper-zinc-based catalyst molded body obtained by impregnating once with a hydrophilic impregnation solution containing an amount of copper corresponding to 1.5 wt% of the total weight of the catalyst. Figure 2c is a graph showing the distribution of copper and zinc loading across the diameter of the catalyst molded body starting from one surface of Figure 2a, based on energy dispersive spectral analysis. Figure 3 shows the CuKα X-ray powder diffraction of the eggshell copper-zinc-based catalyst according to the present invention, contrasted with the standard X-ray diffraction signal positions of copper metal, zinc oxide, and alumina. Figures 4a and 4b show scanning transmission electron microscope (STEM) images of the eggshell-shaped copper-zinc-based catalyst of the present invention shown in Figures 1a and 1c, respectively, and mapping results of the metal atoms (Al, Cu, Zn) constituting it. FIG. 5a is the nitrogen isotherm curve of the eggshell copper-zinc-based catalyst of the present invention, and FIG. 5b shows the pore size distribution of the catalyst. Figure 6 is a graph showing how the methanol conversion rate varies with space velocity at a reaction temperature of 260°C in a methanol vapor reforming reaction with a vapor-to-carbon ratio of 1.5, catalyzed by the eggshell copper-zinc-based catalyst and the homogeneous supported catalyst of the present invention, respectively. Figure 7 is a graph showing how the amount of hydrogen generated varies with space velocity at a reaction temperature of 260°C in a methanol vapor reforming reaction with a vapor-to-carbon ratio of 1.5, catalyzed by the eggshell copper-zinc-based catalyst and the homogeneous supported catalyst of the present invention, respectively. Figure 8 is a graph showing how the specific gravity of carbon monoxide in the reaction effluent composition changes with space velocity at a reaction temperature of 260°C in a methanol vapor reforming reaction with a vapor-to-carbon ratio of 1.5, catalyzed by the eggshell copper-zinc-based catalyst and the homogeneous supported catalyst of the present invention, respectively. Specific details for implementing the invention

[0023] Embodiments of the present invention will be described in detail below. Prior to this, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings. Instead, based on the principle that the inventor can appropriately define the concepts of terms to best describe his invention, they should be interpreted in a meaning and concept consistent with the technical spirit of the present invention.

[0024] Therefore, the embodiments described in this specification are merely examples presented for the purpose of helping to understand the invention and do not represent all technical ideas of the invention; thus, it should be understood that various equivalents and modifications that can replace them may exist at the time of filing this application.

[0025] Unless otherwise defined, all technical terms used in this invention are used in the sense generally understood by a person skilled in the art related to this invention. While preferred methods or samples are described herein, similar or equivalents are also included within the scope of this invention. Numerical values ​​described herein are deemed to include the meaning of "approximately" unless explicitly stated otherwise. Numerical ranges indicated by the term "to" in this specification include ranges that include the values ​​described before and after the term "to" as lower and upper limits, respectively.

[0026] In one aspect of the present invention, a copper-zinc eggshell-shaped catalyst supported on a mesoporous alumina carrier and a molded body of the catalyst are provided.

[0027] In this specification, the term "eggshell catalyst" refers to a catalyst having a structure in which one or more catalytically active metals are not uniformly distributed within a catalyst support but are concentrated on the surface, forming a single layer, and the corresponding catalytically active metals are substantially absent within the catalyst compared to this layer. In such an eggshell catalyst, the thickness of the layer (outer layer) is typically, for example, 1000 μm or less, preferably 800 μm or less, and more preferably 500 μm or less. The thickness of this outer layer and the boundary between the center and the outer layer can be measured from the cross-section of the catalyst using scanning electron microscopy, electron probe microanalysis (EPMA), or optical microscopy.

[0028] The copper-zinc eggshell catalyst of the present invention is a catalyst in which copper and zinc are supported on a mesoporous alumina support. The eggshell catalyst of the present invention consists of a center and an outer layer surrounding the center. In the eggshell catalyst of the present invention, the ratio of the thickness of the outer layer to the length of the major axis of the catalyst or catalyst molded body is 0.30 to 0.54. In the present invention, the major axis of the catalyst or the major axis of the catalyst molded body refers to the axis in the direction having the longest dimension in the shape of the catalyst or catalyst molded body, for example, if the shape of the catalyst or catalyst molded body is an ellipsoid, it refers to the major axis; if the shape is a rectangle, it refers to the longest axis among the three orthogonal axes; and if the shape is a spherical catalyst, it refers to the diameter.

[0029] In the copper-zinc eggshell catalyst of the present invention, copper is substantially present only in the outer layer. In this specification, the statement that copper is substantially present only in the outer layer means that the average copper loading in the center of the eggshell catalyst of the present invention is 0.25 weight% or less. In this specification, when indicating the copper loading in any relevant region or the entire catalyst, unless specifically otherwise indicated, it is always expressed as the percentage that the total weight of copper atoms in that region occupies relative to the total weight of the catalyst, based on the total weight of the final catalyst. The copper loading in the center and outer layer of the eggshell catalyst can be measured by methods known in the art and is not particularly limited; for example, it can be quantified by analyzing the entire catalyst or a relevant part using energy dispersive spectroscopy (EDS) analysis or by analyzing the emission signal at a wavelength of 327.393 nm using inductively coupled plasma emission analysis (ICP-OES). In a more specific embodiment, the eggshell catalyst of the present invention has copper substantially present only in the outer layer, with copper present in the center at 0.2 weight% or less.

[0030] In the copper-zinc eggshell-shaped catalyst of the present invention, the loading amount of copper is 0.85% to 2.8% by weight relative to the total catalyst or the total weight of the molded catalyst body. If the loading amount of copper in the eggshell-shaped catalyst exceeds 2.8% by weight, copper clumps together due to sintering, resulting in poor dispersion, reduced activity, and increased carbon monoxide generation.

[0031] In the copper-zinc eggshell-shaped catalyst of the present invention, the thickness of the outer layer is in the range of 0.35 to 0.48 with respect to the major axis length of the catalyst.

[0032] In the copper-zinc eggshell catalyst of the present invention, zinc exists in the state of zinc (II) with an oxidation number of 2. In one embodiment, the copper-zinc eggshell catalyst of the present invention has a distribution in which the ratio of the loading amount in the center to the loading amount in the outer layer between the center and the outer layer is 0.75 to 1.25.

[0033] In one embodiment of the present invention, the copper-zinc eggshell-shaped catalyst is a catalyst molded body. In one specific embodiment of the present invention, the catalyst molded body is a shape selected from the group consisting of spherical, cylindrical, hexahedral, and ellipsoidal shapes. In a more specific embodiment, the catalyst molded body is a catalyst in which copper and zinc are supported within a pre-molded mesoporous alumina carrier.

[0034] In one specific embodiment of the copper-zinc eggshell-shaped catalyst or catalyst molded body of the present invention, the amount of copper loaded is 0.95 wt% to 2.75 wt% based on the total weight of the catalyst or catalyst molded body.

[0035] In another specific embodiment of the copper-zinc eggshell-shaped catalyst or catalyst molded body of the present invention, the ratio of the outer layer thickness to the major axis length of the catalyst (molded body) is 0.35 to 0.48. In a more specific embodiment, the ratio of the outer layer thickness to the major axis length of the catalyst (molded body) is 0.36 to 0.45.

[0036] In another specific embodiment of the copper-zinc eggshell-shaped catalyst or catalyst molded body of the present invention, the ratio of the amount of copper loaded to the amount of zinc (II) loaded in the catalyst is 0.5 to 2 in molar ratio under the aforementioned weight-based copper loading limit. In a more specific embodiment of the present invention, the ratio of the amount of copper loaded to the amount of zinc (II) loaded in the catalyst is 1 to 2 in molar ratio. If the amount of copper loaded is in the range of 0.5 to 2 in molar ratio to the amount of zinc loaded, it is possible to prevent the sintering of copper particles in the catalyst, thereby reducing the size of copper and zinc particles within the catalyst pores and allowing for high dispersion. Furthermore, it is advantageous to prevent a decrease in activity due to the sintering of copper particles during long-term operation, thereby fully exhibiting the catalytic activity of the methanol vapor reforming reaction. If the molar ratio of the copper loading amount to the zinc (II) loading amount is less than 0.5, the composition is such that zinc (II) is in excess compared to the amount of copper, which is the active material. If the molar ratio exceeds 2, the copper in the catalyst becomes easier to sinter, which can increase the particle size and decrease activity.

[0037] In another specific embodiment of the copper-zinc eggshell-shaped catalyst or catalyst molded body of the present invention, the catalyst (or catalyst molded body) has copper particles of a fine size that does not emit an X-ray diffraction signal.

[0038] The relationship between particle size and the width of the X-ray diffraction signal is given by the Scherrer equation below,

[0039]

[0040] Here, τ is the size of the crystalline particle, θ is the Bragg angle at which the X-ray diffraction signal of the particle is observed, β is the full width half maxima (FWHM) of the signal at a height corresponding to half the signal intensity of the X-ray diffraction signal, K is the Scheerer constant which is determined by the shape of the particle and has a value of 0.94 for spherical crystallites under cubic symmetry, and λ is the wavelength of the X-ray source which is 1.54056 Å for Cu Kα radiation.

[0041] In the present invention, the fact that the size of the copper or zinc (II) particles is a fine size that does not emit an X-ray diffraction signal indicates that the size of β is below the detection limit.

[0042] More specifically, the fact that the size of the copper particles is a fine size that does not emit an X-ray diffraction signal is that when the copper-zinc eggshell-shaped catalyst (or molded body) of the present invention is irradiated with X-rays from a Cu Kα light source, the peak corresponding to the Cu (111) crystal plane in the powder X-ray diffraction (2 according to the JCPDC standard) θ = 43.3° position) indicates that the intensity of this peak is less than or equal to twice the baseline average intensity value in the X-ray diffraction pattern where this peak was measured.

[0043] In another specific embodiment of the copper-zinc eggshell catalyst or catalyst molded body of the present invention, the catalyst (or catalyst molded body) has zinc(II) particles of a fine size that does not emit an X-ray diffraction signal. More specifically, the fact that the zinc(II) particles are of a fine size that does not emit an X-ray diffraction signal is that when the copper-zinc eggshell catalyst or catalyst molded body of the present invention is irradiated with CuKα X-rays, the peak of the Zn(II) crystal grain in the powder X-ray diffraction (according to the JCPDC standard 2 θ = 31.7° position) of This indicates that the intensity is less than or equal to twice the baseline average intensity value in the X-ray diffraction pattern where this peak was measured.

[0044] The copper-zinc eggshell-shaped catalyst of the present invention is characterized by having active metal components in the form of fine particles that are highly dispersed within the outer layer.

[0045] The copper-zinc eggshell-shaped catalyst or catalyst molded body for methanol vapor reforming of the present invention described above can be implemented in two forms: a copper (0) form and a copper (II) form. In one embodiment, the copper is copper with an oxidation state of 2, i.e., divalent copper (II). In this embodiment, the copper-zinc eggshell-shaped catalyst or catalyst molded body of the present invention is a catalyst or catalyst molded body comprising a central part containing zinc (II) and copper (II) supported in a mesoporous alumina carrier formed therein, and an outer layer surrounding said central part, wherein copper (II) is substantially present only in said catalyst or catalyst molded body, and the ratio of the thickness of said outer layer to the major axis length of said catalyst or catalyst molded body is 0.30 to 0.54, and the amount of copper (II) supported in said catalyst or catalyst molded body is 0.85 weight% to 2.8 weight% based on the total weight of said catalyst or catalyst molded body.

[0046] In another embodiment of the copper-zinc eggshell catalyst of the present invention, the copper is metallic copper (0) with an oxidation state of 0. In this embodiment, the copper-zinc eggshell catalyst or catalyst molded body for methanol vapor reforming of the present invention is a catalyst or catalyst molded body comprising a central part containing zinc (II) and copper (0) supported in a mesoporous alumina carrier formed therein, said central part, said catalyst or catalyst molded body, wherein the copper (0) is substantially present only in the outer part, said outer part has a thickness ratio of 0.30 to 0.54 relative to the major axis length of said catalyst or catalyst molded body, and the amount of copper (0) supported in said catalyst or catalyst molded body is 0.85 wt% to 2.8 wt% based on the total weight of said catalyst or catalyst molded body. A copper-zinc eggshell catalyst or catalyst molded body in the form of copper (0) can also be obtained by reducing a copper-zinc eggshell catalyst or catalyst molded body in the form of copper (II).

[0047] In one aspect of the present invention, a copper-zinc eggshell-shaped catalyst supported on a mesoporous alumina carrier capable of catalyzing a methanol steam reforming reaction is provided, and a method for manufacturing such a catalyst molded body. The manufacturing method of the present invention utilizes the incompatibility between a hydrophobic solvent and a hydrophilic solvent to selectively support or impregnate a catalytically active material only on the surface of the molded alumina carrier or in the pores of the external region connected to the surface. By controlling the degree of miscibility between the hydrophobic solvent and the hydrophilic solvent, the removal conditions of the hydrophobic and / or hydrophilic solvent, and the concentration of the copper and / or zinc precursor in the hydrophilic solvent, it is possible to easily selectively impregnate copper, which is catalytically active, only to the surface of the alumina and to a predetermined depth to a desired level.

[0048] The method for manufacturing a mesoporous alumina-supported copper-zinc-based catalyst for methanol steam reforming according to the present invention

[0049] i) a hydrophobic immersion step of immersing mesoporous alumina in a solvent selected from the group consisting of ethylene glycol, propylene glycol, diethylene glycol, and glycerol, or a mixture thereof,

[0050] ii) copper precursor and,

[0051] An impregnation step of immersing the mesoporous alumina that has completed the hydrophobic immersion step in an aqueous solution containing a zinc precursor in an amount of zinc precursor containing 0.5 to 2 times the number of moles of copper atoms in the copper precursor,

[0052] iii) a drying step for drying the mesoporous alumina after the above impregnation step, and

[0053] iv) Includes a calcination step of calcining the dried mesoporous alumina.

[0054] In one embodiment of the manufacturing method of the present invention, a copper-zinc eggshell catalyst supported on mesoporous alumina is manufactured by using an aqueous solution (impregnation solution) containing a copper precursor at a concentration close to the target final copper loading amount in the copper-zinc eggshell catalyst and performing steps i) to iv) only once (single impregnation). In another embodiment of the manufacturing method of the present invention, a copper-zinc eggshell catalyst supported on mesoporous alumina is manufactured by using an aqueous solution (impregnation solution) containing a copper precursor at a concentration less than the target final copper loading amount, and repeating steps i) to iv) above to reach the copper loading amount in the outer layer of the copper-zinc eggshell catalyst (repeated impregnation).

[0055] In the hydrophobic immersion step, which is the first step of the manufacturing method of the present invention, mesoporous alumina to be used as a catalyst carrier is immersed in a hydrophobic solvent. In the hydrophobic immersion step, the pores inside the alumina are filled with the hydrophobic solvent. While performing the hydrophobic immersion step, an active stirring method, such as sonication, can be used to allow the hydrophobic solvent to sufficiently penetrate into the alumina carrier. Mesoporous alumina may be alumina with an internal pore diameter in the range of 2 to 50 nm in accordance with the classification of the International Union of Pure and Applied Chemistry (IUPAC), and although not particularly limited, mesoporous gamma alumina may be cited as a specific example. In a more specific embodiment, this mesoporous alumina is an alumina molded body or pellet formed by molding alumina powder into a shape selected from spherical, cylindrical, hexahedral, and ellipsoidal. In the most specific embodiment, the mesoporous alumina may be heat-treated before hydrophobic immersion to ensure that the pores are completely empty. The heat treatment conditions are not particularly limited and can be appropriately determined by a person skilled in the art; for example, heat treatment may be performed at 500°C for 5 hours. In the hydrophobic immersion step, the first immersion step is performed by immersing the mesoporous alumina carrier until no bubbles are generated. The first immersion step may be appropriately controlled by considering the pore size and porosity of the catalyst carrier, the type and viscosity of the first hydrophobic solvent, and the surface tension with the catalyst carrier.

[0056] The hydrophobic solvent that can be used in the hydrophobic immersion step of the manufacturing method of the present invention is one solvent selected from the group consisting of ethylene glycol, propylene glycol, diethylene glycol, and glycerol, or a mixture of these solvents.

[0057] The performance of the hydrophobic immersion step is not limited to a specific method and can be appropriately controlled by a person skilled in the art; for example, it can be performed by immersing a mesoporous alumina carrier at room temperature until no bubbles are generated. The hydrophobic immersion step can be appropriately controlled by considering the pore size and porosity of the alumina carrier, the type and viscosity of the hydrophobic solvent, and the surface tension with the alumina.

[0058] In one specific embodiment of the manufacturing method of the present invention, an intermediate drying step may be added as needed before proceeding with the impregnation step after completing the hydrophobic immersion step. By including an intermediate drying step, the depth to which the hydrophobic solvent is left within the central pores of the alumina particles (or alumina molded bodies) before entering the impregnation step can be controlled, thereby contributing to more precise control of the outer layer thickness of the eggshell catalyst. The drying temperature and drying time of the intermediate drying step can be appropriately adjusted by an average skilled person in the art through repeated testing depending on the extent to which the hydrophobic solvent is to be removed from the mesoporous alumina. Although not particularly limited, it is appropriate to carry out the drying at a temperature in the range of 50°C or lower to 50°C or higher based on the boiling point of the hydrophobic solvent used in the hydrophobic immersion step, and for a period of 1 minute to 120 minutes.

[0059] In the manufacturing method of the present invention, the impregnation step is a process of filling the surface region and the outer pore region near the surface of the mesoporous alumina, which has been hydrophobically immersed in an aqueous solution containing a copper precursor and a zinc precursor, with said copper precursor and zinc precursor by utilizing the incompatibility between water and a hydrophobic solvent.

[0060] Water-soluble salts of copper and zinc and their hydrates can be used as copper and zinc precursors for the impregnation step. Suitable examples of precursor salts include copper(II) nitrate (Cu(NO3)2) and zinc(II) nitrate (Zn(NO3)2).

[0061] In the impregnation step of the manufacturing method of the present invention, the mesoporous alumina is immersed using an impregnation solution, which is an aqueous solution containing the aforementioned copper precursor and zinc precursor, and the content of the copper precursor and zinc precursor in this impregnation solution is determined based on copper and zinc atoms. As previously described, impregnation can be performed by immersing the mesoporous alumina only once (single impregnation) in an impregnation solution containing a copper precursor in an amount that contains copper atoms, which are the active components of the copper-zinc eggshell catalyst for methanol steam reforming, to the target final loading amount within the catalyst. Alternatively, the impregnation can be performed by repeatedly immersing the mesoporous alumina in an impregnation solution containing a copper precursor in an amount that contains less copper atoms than the target final loading amount within the catalyst (repeated impregnation) to reach the target final loading amount within the catalyst. When determining the content of the copper precursor to be used in the impregnation solution according to a single impregnation or repeated impregnation method, it is appropriate to include the zinc precursor in the impregnation solution in an amount containing 0.5 to 2 times the number of zinc atoms relative to the number of moles of copper atoms in the copper precursor content. For example, if the target amount of copper atoms loaded in the outer layer of the eggshell catalyst is around 2.5 wt% (weight percentage of the weight of copper atoms relative to the total weight of the eggshell catalyst) and five repeated impregnations are considered, the impregnation solution may repeatedly use an aqueous solution in which an amount of copper precursor capable of providing a number of copper atoms corresponding to 0.5 wt% of the total weight of the catalyst is dissolved in an appropriate amount of water. At this time, the amount of the zinc precursor in the impregnation solution may be determined as an amount containing zinc atoms selected from among 0.5 to 2 times the number of moles of copper atoms corresponding to the above 0.5 wt%. In a more specific embodiment, the content of the copper precursor in the impregnation solution is suitable to be a value in the range such that the total weight of copper atoms in the content is 0.1 weight% or more and 1.0 weight% or less with respect to the total weight of the copper-zinc eggshell-shaped catalyst to be manufactured.In the most specific embodiment, the content of the copper precursor in the impregnation solution is such that the sum of the weights of copper atoms among the copper precursors present in the impregnation solution is 0.1 wt% or more and 1.0 wt% or less as described above, and at the same time, the content is such that the target copper loading amount in the copper-zinc eggshell catalyst to be manufactured is less than or equal to half of the target copper loading amount. Accordingly, the target copper loading amount is reached by repeating the impregnation as many times as necessary to reach the target copper loading amount, that is, by repeating the steps (1) to (4) described above as many times as necessary. At this time, the sum of the weights of copper atoms and the target copper loading amount described above are both defined as weight percentages relative to the total weight of the copper-zinc eggshell catalyst. For example, when the target copper loading amount in the copper-zinc eggshell catalyst to be manufactured is 2.5% by weight of the total weight of the catalyst, the copper precursor content in the impregnation solution can be used such that the sum of the weights of the copper atoms contained therein is less than or equal to half of 2.5% by weight, for example, the sum of the weights of the copper atoms is 0.5% by weight of the total weight of the catalyst. In this case, the number of repeated impregnations can be as many as necessary, for example, 2.5 × 0.5 = 5 times or more, until the corresponding copper loading amount is reached.

[0062] The concentrations of the copper precursor and zinc precursor in the aqueous solution (impregnation solution) and the immersion temperature in step ii) above can be appropriately adjusted according to the type of precursor used, the target loading amount, the target thickness of the eggshell-shaped catalyst outer layer, the viscosity of the impregnation solution, the porosity and pore distribution of the alumina support, the alumina surface tension, etc. Generally, the concentration of the copper precursor in the impregnation solution is approximately 0.01 M to 0.5 M, the immersion temperature range is from room temperature to 90°C, and the immersion time is within the range of 10 to 60 minutes, allowing for single or repeated immersion. Impregnation can be performed using a rotary device such as a rotary evaporator.

[0063] In the manufacturing method of the present invention, a drying step and a calcination step are performed following the impregnation step. The mesoporous alumina that has completed the impregnation step has a region filled with the hydrophobic solvent in its center, and an outer layer surrounding the center and extending to the surface is filled with the impregnation liquid; in the drying step, this hydrophobic solvent and water are removed. In the manufacturing method of the present invention, the temperature and time of the drying step are not particularly limited; a temperature and time sufficient to adequately remove the hydrophobic solvent and water from within the pores of the mesoporous alumina that has completed the impregnation step are sufficient, and a person skilled in the art can set them through appropriate experiments without technical difficulty. For example, the alumina, alumina molded body, or alumina pellet that has completed the impregnation step may be transferred and dried at 130°C for 12 hours.

[0064] The subsequent calcination step serves to convert the impregnated copper precursor and zinc precursor into their corresponding oxides, and it is appropriate to perform this step in air at a temperature range of 250 to 400°C. The copper-zinc eggshell catalyst of the present invention has the advantage of reducing the amount of byproduct gases (e.g., nitrogen oxides) released during the calcination step because it can have a lower absolute loading amount of copper and zinc within the catalyst than a uniformly loaded catalyst.

[0065] In one embodiment of the manufacturing method of the present invention, a reduction step may be further provided after the calcination step. The calcined catalyst (or catalyst precursor) in which copper and zinc are supported on mesoporous alumina, or the molded body thereof, or the catalyst pellet, may be manufactured as a pre-reduced catalyst that undergoes a step of reducing copper (II) to copper (O). Alternatively, this reduction step may be performed by transferring the calcined catalyst (or catalyst precursor) in which copper and zinc are supported on mesoporous alumina, or the molded body thereof, or the catalyst pellet, into a reactor where a methanol steam reforming reaction takes place, and reducing it in situ immediately before the reforming reaction. in situIt can also be done in a reduction manner.

[0066] The reduction step can be carried out using a hydrogen-containing gas, and a person skilled in the art can find the optimal conditions through repeated experiments. For example, the reduction step can be carried out by applying a hydrogen-containing gas stream selected from pure hydrogen, synthesis gas, or a mixture of inert gases such as hydrogen and nitrogen to the catalyst (or catalyst precursor) that has completed the aforementioned calcination step for an appropriate time, for example, 1 to 24 hours, at an appropriate temperature, for example, 200 to 400°C, at a pressure in the range of atmospheric pressure to 25 bar.

[0067] The manufacturing method of the present invention allows for the easy preparation of an eggshell-shaped catalyst in which the active material, copper, is substantially absent in the center by using a simple method that utilizes the incompatibility between a hydrophobic solvent and water. In particular, using repeated impregnation offers the advantage of securing a distinct eggshell distribution of the active material at high copper loadings, which is difficult to obtain with single impregnation, while also enabling fine dispersion of copper particles.

[0068] [Example]

[0069] The present invention will be explained in more detail below through the following examples and experimental examples. However, these examples and experimental examples are intended only to aid in understanding the present invention and do not limit the scope of the present invention in any way. Various changes and modifications may be made to these examples, and such changes and modifications are also included within the scope of the appended claims.

[0070] Preparation Example: Preparation of alumina-supported eggshell-shaped copper-zinc catalyst and homogeneous metal-supported copper-zinc catalyst

[0071] As copper-zinc-based catalysts, a homogeneous supported catalyst in which copper metal is supported relatively uniformly across the entire support and an eggshell-shaped catalyst in which it is supported only on the surface and up to a predetermined depth were prepared. Gamma alumina spherical pellets (manufacturer: Sasol, South Africa; average diameter 3 mm) were used as the support. These alumina pellets had a BET specific surface area of ​​200 m² 2 / g, pore volume 0.53 cm³ 3 It was a mesoporous material with properties of / g and an average pore size of about 8 nm. Before impregnating the metal into the carrier pellet, the pellet (30 g) was heat-treated at 500°C for 5 hours to make the interior hollow.

[0072] (1) Preparation of copper-zinc eggshell catalyst

[0073] 30 g of the heat-treated carrier was immersed in ethylene glycol and ultrasonically dispersed for 50 minutes to perform hydrophobic wet immersion. Before proceeding with the impregnation step, 30 g of the carrier immersed in the ethylene glycol solution was removed using a sieve.

[0074] Subsequently, impregnation was carried out using a hydrophilic impregnation solution containing a predetermined amount of copper precursor and an equal number of moles of zinc precursor. In the preparation of the hydrophilic impregnation solution, an aqueous solution of an amount of copper precursor and an equal number of moles of zinc precursor was used such that, assuming full impregnation, the weight percentage of copper relative to the total weight of the catalyst was 0.5 wt%. Specifically, 0.62 g of copper nitrate trihydrate [Cu(NO3)2·3H2O] and 0.76 g of zinc nitrate hexahydrate [Zn(NO3)2·6H2O] were dissolved as precursors in 30 mL of deionized water using a stirrer (300 rpm, 1 min), and the pellet that had completed the hydrophobic impregnation was immersed in this solution and heated at 80°C for 30 minutes. Hydrophilic impregnation was performed using a rotary evaporator. Subsequently, the pellets were transferred to a Petri dish and dried at 130°C for 12 hours, followed by calcination at 350°C for 3 hours under an atmospheric setting (heating rate: 2.5°C per minute). The number of repetitions of this process was varied to a total of 6 times (Comparative Example 3), 5 times (Example 1), 4 times (Example 2), 3 times (Example 3), and 2 times (Example 4) to adjust the approximate copper loading relative to the total weight of the catalyst to 2.5 wt%, 2 wt%, and 1.5 wt%, respectively. Subsequently, the loaded pellets were subjected to a reduction treatment in which a 40% hydrogen-nitrogen stream was applied at 300°C for 1.5 hours to complete the eggshell catalyst molded body.

[0075] (2) Preparation of copper-zinc homogeneous supported catalyst

[0076] An aqueous solution of a copper precursor in an amount such that the weight percentage of copper relative to the total catalyst weight is 0.5 wt%, assuming complete impregnation, and an equal molar amount of a zinc precursor were used. Specifically, 0.62 g of copper nitrate trihydrate [Cu(NO3)2·3H2O] and 0.76 g of zinc nitrate hexahydrate [Zn(NO3)2·6H2O] were dissolved as precursors in 30 mL of deionized water using a stirrer (300 rpm, 1 min), and the heat-treated pellet was immersed in this solution and subjected to 80°C for 30 minutes. Hydrophilic impregnation was performed using a rotary evaporator. Subsequently, the pellets were transferred to a Petri dish and dried at 130°C for 12 hours, followed by calcination at 350°C for 3 hours under an atmospheric setting (heating rate: 2.5°C per minute). The number of times this process was repeated was varied to a total of 10 times (Comparative Example 1) and 5 times (Comparative Example 2) to adjust the approximate copper loading relative to the total weight of the catalyst to 5 wt% and 2.5 wt%, respectively. Subsequently, the loaded pellets were subjected to a reduction treatment in which a 40% hydrogen-nitrogen stream was applied at 300°C for 1.5 hours to complete the eggshell catalyst molded body.

[0077] (3) Single-step impregnation catalyst preparation

[0078] A catalyst (Comparative Example 4) was prepared in the same manner as the eggshell-shaped catalyst described above, except that hydrophobic impregnation and hydrophilic impregnation were performed on 30 g of heat-treated carrier, with the concentration of the copper precursor in the hydrophilic impregnation solution being 1.5 wt% of the total catalyst amount and the concentration of the zinc precursor being the same molar concentration as the copper precursor, and the hydrophilic impregnation, drying, calcination, and reduction were performed once without a repeated process.

[0079] [Analysis Example 1] Metal distribution in catalyst molded body

[0080] The distribution pattern of copper was observed by using an optical microscope to examine the cross-sections of the eggshell-shaped catalyst and the homogeneous supported catalyst prepared in the preparation example, utilizing the repulsive force between the hydrophobic solvent and the hydrophilic metal precursor. Figures 1a to 1c, which show the cross-sections of the catalyst molded bodies of Examples 1 to 3, respectively, showed a distinct contrast between the black outer layer visible around the perimeter of the pellet and the white center existing in the middle of the pellet. Since the black color of the catalyst molded body pellet represents reduced copper in a metallic state (0 valence), it was possible to infer an eggshell copper metal distribution in which almost no copper metal was present in the white center. In contrast, Figures 2a and 2b, which show the cross-sections of the catalyst molded bodies of Comparative Example 1 and Comparative Example 4, were filled only with black, and the appearance of the homogeneous supported copper catalyst was such that the outer layer and the center could not be distinguished. The catalyst of Comparative Example 4 has a copper loading amount that is less than that of the eggshell catalysts of Example 1 or Example 2 and is equivalent to that of the eggshell catalyst of Example 3, but is obtained by impregnating once with a copper precursor impregnation solution containing an amount of copper atoms corresponding to 1.5 wt% of the total weight of the catalyst, and for this reason, the copper metal does not form an eggshell layered structure and is formed as a homogeneous supported catalyst (Fig. 2b).

[0081] For the catalyst of Example 1, representing the eggshell-shaped catalyst obtained in the above preparation example, and the catalyst of Comparative Example 1, representing the homogeneous supported catalyst, the distribution of copper and zinc across the width of the pellet diameter was observed using field emission scanning electron microscopy (FE-SEM) and energy dispersive spectroscopy (EDS). When examining the distribution of copper and zinc across the diameter width of the eggshell-shaped catalysts of Example 1 shown in Fig. 1e and Example 3 shown in Fig. 1f, copper was not observed when the depth of penetration from both surfaces of the pellet was approximately 400 μm or more, indicating that it was localized in the outer layer, whereas zinc was distributed relatively uniformly across the entire width of the pellet. In contrast, Comparative Example 1, the homogeneous supported catalyst shown in Fig. 2c, showed both copper and zinc evenly distributed across the diameter width of the pellet.

[0082] The actual copper and zinc loading amounts of the catalysts in Examples 1 to 4 and Comparative Examples 1 and 3 obtained from the preparation examples were quantified by inductively coupled plasma emission analysis (ICP-OES). For the analysis of copper, emission lines with wavelengths of 327 and 393 nm were used, and for the analysis of zinc, emission lines with wavelengths of 206.2 nm were used. The loading amounts of copper or zinc were expressed as the weight percentage of the corresponding metal relative to the total weight of the catalyst and summarized in Table 1.

[0083]

[0084] From the results shown in Table 1, it can be seen that the actual amount of copper loaded in the catalyst is close to the value expected from repeated wet impregnation with an impregnation solution of 0.5 wt%.

[0085] Table 2 summarizes the ratio of the outer layer thickness of the catalyst in Examples 1 to 4 to the major axis length of the catalyst molded body and the ratio of the amount of copper (0) loaded in the center to the total weight of the catalyst molded body, measured by energy dispersive spectroscopic analysis.

[0086]

[0087] The catalysts of Examples 1 to 4 followed the ratio of the thickness of the outer layer to the length of the major axis of the present invention, and copper (0) was not detected in the center, confirming that they had distinct characteristics as eggshell-shaped catalysts.

[0088] [Analysis Example 2] Dispersion of copper and zinc particles in eggshell-shaped catalyst

[0089] To examine the particle dispersion state of the eggshell catalysts of Examples 1 to 3, analysis was performed using powder X-ray diffraction, scanning transmission electron microscopy (STEM), and energy dispersive spectroscopy (EDS). CuKα (wavelength 1.54056 Å) was used as the light source for X-ray diffraction, and the positions of the diffraction peaks were compared to the standards according to the Joint Committee on Powder Diffraction Standards (JCPDS).

[0090] As can be seen in FIG. 3, in the X-ray diffraction patterns of the catalysts of Examples 1 to 3, the JCPDS diffraction peak positions corresponding to copper and zinc (II) in the metallic state (corresponding to the copper (111), (200) and (220) crystal plane signals under the CuKα light source, respectively) θ At values ​​of 43.3°, 50.4°, and 74.1°, no diffraction signals of the corresponding catalysts were observed. That is, these catalysts were at a position corresponding to the metallic Cu(111) crystal plane (near 43.3° according to JCPDS). The peak intensity was 1.4 times or less compared to the average intensity value of the corresponding X-ray diffraction baseline, and at a location that could be distinguished from the signal of the alumina carrier (2 θ = No zinc (II) signal was detected at 31.7°. These results show that although copper exists in a zero-valence metallic state within the eggshell catalyst of the present invention, the copper metal particles have not grown to a size large enough to produce an X-ray diffraction signal through sintering.

[0091] In Figures 4a and 4b, which show STEM images and metal atom mapping analysis by EDS for the catalysts of Example 1 and Example 3, it was confirmed that the copper and zinc particles were small and evenly distributed. These results in Figure 4 are consistent with the X-ray diffraction data in Figure 3 and indicate that copper and zinc are highly dispersed within the eggshell copper-zinc catalyst of the present invention.

[0092] [Analysis Example 3] Pore diameter

[0093] The pore size distribution was measured for the eggshell-shaped catalysts of Examples 1 to 3. The pore size distribution was analyzed using the Barrett-Joiner-Halendar (BJH) method based on the desorption curve from the nitrogen adsorption-desorption measurements, and the results are shown in Figures 5a and 5b. As can be seen from the nitrogen adsorption-desorption isotherm curve in Figure 5a, the catalysts of Examples 1 to 3 all exhibited behavior forming hysteresis rings (Type 4 according to the International Union of Pure and Applied Chemistry (IUPAC) classification) of the same type as the untreated alumina carrier, confirming that they possess cylindrical pores identical to those of the untreated alumina carrier. Furthermore, the tendency of the nitrogen adsorption amount to decrease as the metal loading amount increases in Figure 5a indicates that copper metal and zinc oxide particles have evenly penetrated into the pores of the alumina carrier. And from the BJH method pore distribution graph shown in Fig. 5b, the pore size distribution of Examples 1 to 3 showed a distribution centered at 8 nm, which is substantially the same position as the untreated alumina carrier.

[0094] From the aforementioned results, it was confirmed that the eggshell-shaped copper-zinc catalyst of the present invention can achieve high dispersion of copper and zinc while maintaining the pore structure of the mesoporous alumina carrier regardless of the copper loading amount.

[0095] [Experimental Example] Methanol Steam Reforming Reaction

[0096] The catalytic performance of the homogeneous supported catalysts of Comparative Examples 1 and 2 and the catalysts of Examples 1 to 3 for the methanol steam reforming reaction was evaluated. The catalysts of the Comparative and Examples used in the methanol reforming reaction were prepared by in situ (a fixed-bed reactor equipped with an Inconel pipe with a thickness of 26 mm (inner diameter 23 mm)) using 12 g each of copper-zinc supported alumina that had not undergone the reduction treatment of the final step of the aforementioned preparation example, in the same manner immediately before the reaction. in situ The catalyst was completed by reducing ). In this methanol steam reforming reaction, feedstock vapor was supplied to the reactor by first heating the reactants to 160°C to vaporize them, and a reactant stream with a steam-to-carbon ratio (steam ratio to methanol) of 1.5 was supplied at a rate of 5 g / g per hour under a reactor temperature of 260°C. 촉매 Up to 18 g / g 촉매 The reaction was carried out while varying the space velocity. The products were analyzed by gas chromatography. The methanol conversion rate was calculated as the ratio of the sum of the carbon monoxide and carbon dioxide fractions exiting the reactor to the introduced methanol fraction.

[0097] Figure 6 shows the relationship between the methanol conversion rate and space velocity, which are the reactants of the methanol steam reforming reaction, and Figure 7 shows the relationship between the hourly generation rate of hydrogen per unit catalyst weight, which is the product, and space velocity. Both the eggshell catalyst of the example and the homogeneous supported catalyst of the comparative example showed a tendency for the methanol conversion rate to decrease and the hydrogen generation rate to increase as the space velocity increased. As clearly shown in the comparison of Example 1 and Comparative Example 2 in Figures 6 and 7, between the eggshell catalyst and the homogeneous supported catalyst having the same copper loading amount, the methanol conversion rate and hydrogen generation rate of the eggshell catalyst were significantly higher. Although the homogeneous supported catalyst of Comparative Example 1 had a higher methanol conversion rate and hydrogen generation rate than the eggshell catalyst of Example 1, considering that the copper loading amount was double, the efficiency per unit copper content of the eggshell catalyst of Example 1 was higher than that of Comparative Example 1.

[0098] Looking at the graph of the proportion of carbon monoxide in the product composition according to the space velocity shown in Fig. 8, it can be seen that the eggshell catalyst of the present invention is superior to the homogeneous supported catalyst in terms of carbon monoxide generation. The eggshell catalyst of Example 1 significantly suppressed carbon monoxide generation against the homogeneous supported catalyst of Comparative Example 1, which has a higher copper loading amount, and was generally superior against the homogeneous supported catalyst of Comparative Example 2, which has the same loading amount, and exhibited a carbon monoxide generation suppression effect that became superior as the space velocity increased.

[0099] From these results, it was confirmed that the copper-zinc eggshell catalyst of the present invention can lower carbon monoxide generation while possessing superior methanol conversion rate and hydrogen generation compared to a homogeneous supported catalyst with the same copper loading amount in the methanol-water vapor reaction.

[0100] Although the present invention has been described with reference to limited embodiments as above, the technical concept and scope of the present invention are not limited to these aforementioned embodiments. In addition to the invention of the patent claims described below, various modifications or variations of the invention described in the patent claims that are obvious to those skilled in the art to which this invention belongs are also included within the scope of the present invention within the equivalent scope of the invention described in the patent claims.

Claims

Claim 1 A molded catalyst body for methanol vapor reforming containing zinc (II) and copper (O) supported in a molded mesoporous alumina carrier, wherein the molded catalyst body is composed of a center and an outer layer surrounding the center, wherein the ratio of the thickness of the outer layer to the major axis length of the molded catalyst body is 0.30 to 0.54, the amount of copper (O) supported in the molded catalyst body is 0.85 weight% to 2.8 weight% based on the total weight of the molded catalyst body, and the average amount of copper supported in the center of the molded catalyst body is 0.25 weight% or less. Claim 2 A catalyst molded body according to claim 1, characterized in that the ratio of the outer layer thickness to the major axis length of the catalyst molded body is 0.35 to 0.

48. Claim 3 A catalyst molded body according to claim 2, characterized in that the ratio of the outer layer thickness to the major axis length of the catalyst molded body is 0.36 to 0.

45. Claim 4 A catalyst molded body according to claim 1, characterized in that the amount of copper (0) loaded in the catalyst molded body is 0.95 wt% to 2.75 wt% based on the total weight of the catalyst molded body. Claim 5 A catalyst molded body according to claim 1, characterized in that the amount of copper (0) loaded relative to the amount of zinc (II) loaded in the catalyst molded body is 0.5 to 2 in molar ratio. Claim 6 A catalyst molded body according to claim 5, characterized in that the amount of copper (0) loaded relative to the amount of zinc (II) loaded in the catalyst molded body is 1 to 2 in molar ratio. Claim 7 In claim 5, the catalyst molded body is characterized in that when irradiated with CuKα X-rays, the intensity of the peak corresponding to the Cu (111) crystal plane in the powder X-ray diffraction is less than or equal to twice the baseline average intensity value of the X-ray diffraction. Claim 8 A catalyst molded body according to claim 1, characterized in that the center of the catalyst molded body has a loading amount of copper (0) of 0.2 weight% or less of the total weight of the catalyst molded body. Claim 9 In claim 5, the catalyst molded body is characterized in that, when irradiated with CuKα X-rays, the intensity of the peak of the Zn(II) crystal grain in the powder X-ray diffraction is less than or equal to twice the baseline average intensity value of the X-ray diffraction pattern. Claim 10 A catalyst molded body according to claim 1, characterized in that the catalyst molded body has a shape selected from spherical, cylindrical, hexahedron, and ellipsoid. Claim 11 A catalyst molded body for methanol vapor reforming containing zinc (II) and copper (II) supported in a molded mesoporous alumina carrier, wherein the catalyst molded body is composed of a core and an outer layer surrounding the core, wherein copper (II) in the catalyst is substantially present only in the outer layer, wherein the ratio of the thickness of the outer layer to the major axis length of the catalyst molded body is 0.30 to 0.54, wherein the amount of copper (II) supported in the catalyst molded body is 0.85 wt% to 2.8 wt% based on the total weight of the catalyst molded body, wherein the average amount of copper supported in the core of the catalyst molded body is 0.25 wt% or less; and wherein the ratio of the average amount of zinc (II) supported in the outer layer to the average amount of zinc (II) supported in the core is 0.75 to 1.

25. Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete Claim 16 delete Claim 17 delete